Духовность и святость в романе Евгения Водолазкина Лавр - Kamalova, Alla (Acta Polono-Ruthenica, 2018)
The article is devoted to spirituality as an actual category of the scientific and cultural paradigm of the 20th century, spirituality is qualified as an “eternal theme”. The author emphasizes the “fuzziness of the theme,” speaks about the complexity of its definition, as well of ambigious understanding in various socio-historical periods. Spirituality as an eternal topic of fiction is discussed on the example of the novel by Evgenе Vodolazkin Lavr. Lavr – is a hagiographic novel, which describes the life and spiritual path of the doctor in Medieval Russia. The author emphasizes the actuality of the novel Lavr for modern Russia.